2003
DOI: 10.1177/153303460300200513
|View full text |Cite
|
Sign up to set email alerts
|

Viral and Non-viral Vectors in Gene Therapy: Technology Development and Clinical Trials

Abstract: Gene therapy as part of modern molecular medicine holds great promise for the treatment of both acute and chronic diseases and has the potential to bring a revolutionary era to cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 82 publications
0
65
0
2
Order By: Relevance
“…29 Preliminary clinical data from a phase I study with encapsulated SFV-IL-12 particles on kidney carcinoma and melanoma patients suggested that there was no liposome-or SFV-related toxicity or any other adverse events. 28 The IL-12 levels in the serum of patients were transiently increased five-fold with maximal expression after 2 days, with a steady decrease until base levels were reached after 5 days. Repeated administration of encapsulated SFV particles generated no detectable immune response.…”
Section: Alphaviruses In Gene Therapy K Lundstrommentioning
confidence: 94%
See 2 more Smart Citations
“…29 Preliminary clinical data from a phase I study with encapsulated SFV-IL-12 particles on kidney carcinoma and melanoma patients suggested that there was no liposome-or SFV-related toxicity or any other adverse events. 28 The IL-12 levels in the serum of patients were transiently increased five-fold with maximal expression after 2 days, with a steady decrease until base levels were reached after 5 days. Repeated administration of encapsulated SFV particles generated no detectable immune response.…”
Section: Alphaviruses In Gene Therapy K Lundstrommentioning
confidence: 94%
“…The first step towards gene therapy application was the demonstration of high transduction rates of various Large-scale production Drug screening, structural biology 9,10 Primary neurons Localization, electrophysiology 11 Hippocampal slices Localization, electrophysiology 12,13 In vivo, rat brain Localization, duration 16 Gene therapy Cancer vaccines Tumor protection, tumor regression 20 Tumor cell lines Transduction, cell killing 17,18 Intratumoral injection Tumor regression 23,24 Liposome-encapsulation Tumor-targeted gene delivery, therapy 28 18 Clearly, the infection rate was modest, although a bystander effect was observed for the therapeutic TK (thymidine kinase) after ganciclovir treatment. Another application of alphaviruses for cancer therapy has been vaccination with tumor antigens.…”
Section: Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 In spite of their high transduction efficiency, viral vectors are associated with immunogenicity, toxicity and possible mutagenesis of the target cells. 4 Non-viral vectors have become an attractive alternative, [5][6][7] but the low efficiency of transfection results in less efficient targeting of genes to the tissue of interest. The lack of an effective and safe gene targeting vector has become the major barrier to the wide application of gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they have been applied to transfer gene as intraperitoneal injection (e.g., in metastatic ovarian cancer). [40] It has been shown that cationic solid lipid nanoparticles (SLNs) can successfully link to DNA, protect them from degradation by DNase I, and deliver them into cells. The properties of the complexes are dependent on the ratio between particles and nucleic acids.…”
Section: Lipid-based Non-viral Vectorsmentioning
confidence: 99%